The development of real-time daylight sky colour simulation for virtual environment - Sunar, Mohd. Shahrizal; Bade, Abdullah (Faculty of Computer Science and Information System, 2005)
Computer graphics are typically used to generate real-world simulations with realistic image generation, especially for external environments that require sky as the main background. This research study aims to generate simulated sky color during the day which can model the sky from any location on earth. The study only focuses on the color of the sky only without taking into account the other objects in the sky such as clouds, rainbows, atmospheric effects and so on. The domineering or hemisphere method is used in the development of this simulation. Among the important things in determining the sun's position is the time, date and location of the observer. Location of observer is determined by longitude and latitude of the earth. The dom model is used as a representation of the sky. The basic mathematical formula for the sphere is used to model a robust data structure for the dom model. The sky is also calculated using an analytical model for the sky. The calculated sky color will be mapped to the vertices in the dom. Then the color between each vertex will be calculated interpolated and smoothly deluded to produce a color estimate for the sky. This technique has been able to increase performance and improve simulation earnings. Hence, it is best suited to real-time applications and can also contribute to the weather model in the environmental modeling.